Cross-National Patterns of Social Capital Accumulation: Network Resources and Aging in China, Taiwan, and the United States. (July 2015) - McDonald, Steve; Chen, Feinian; Mair, Christine A.
Cultural and institutional context has the potential to moderate life course patterns of social interaction and network connectivity, yet few have attempted to empirically assess this claim. Contrasting collectivist versus individualistic cultural traditions, as well as socialist versus capitalist institutions, we develop and test a set of propositions regarding age-based variation in daily contact, occupational connections, and organizational memberships in China, Taiwan, and the United States. Analyses from cross-sectional survey data reveal how the cultural and institutional differences help structure access to social capital across age. Specifically, the data show how social capital accumulation in the individualistic societies is facilitated by employment and civic institutions, whereas family institutions form the basis for social capital accumulation in collectivist societies.